An electrochemical device

CN122950563APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511179240.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]锂过渡金属氧化物具有高的能量密度,将锂过渡金属氧化物和过渡金属磷酸盐共同作为正极活性材料可以提升能量密度,但是复合之后快充性能及安全性能(高温产气)成为新的问题,急需解决复合体系快充及高温产气问题

Benefits of technology

[0024]本申请中,正极活性材料包括锂过渡金属磷酸盐和锂过渡金属氧化物,电化学装置可以兼顾高能量密度和高安全性能。本申请中在电解质中同步引入羧酸酯和1,3-丙烷磺内酯,羧酸酯可以显著提升快充性能,但是羧酸酯在高电压下会与锂过渡金属氧化物发生副反应,从而导致高温性能(安全性能)劣化。本申请通过引入1,3-丙烷磺内酯,1,3-丙烷磺内酯可以在正极极片表面形成保护膜,阻挡羧酸酯溶剂与锂过渡金属氧化物的接触,由此抑制羧酸酯与锂过渡金属氧化物的副反应,提升电化学装置的高温性能,即进一步提升电化学装置的安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005561344550000111
    Figure BDA0005561344550000111
Patent Text Reader

Abstract

This application discloses an electrochemical device, relating to the field of battery technology. The electrochemical device includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes a positive electrode active material; the positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide; the electrolyte includes additives and an organic solvent. The additives include 1,3-propane sulfonyl lactone, and the organic solvent includes a carboxylic acid ester solvent. This electrochemical device can balance safety and fast-charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, and specifically relates to an electrochemical device. Background Technology

[0002] Electrochemical devices have become the most popular energy storage systems due to their high operating voltage, long lifespan, and environmental friendliness, and are now widely used in pure electric vehicles, hybrid electric vehicles, smart grids, and other fields. However, with technological advancements, more stringent requirements have been placed on the safety performance, kinetic performance, and high-temperature cycling of electrochemical devices.

[0003] Lithium transition metal phosphates (LTM phosphates) are increasingly used in power batteries due to their high safety performance, currently accounting for over 50% of all power battery installations. However, the energy density of LTM phosphates limits their use in long-range electric vehicles and restricts further market expansion. Therefore, improving energy density has become a key issue that needs to be addressed for LTM phosphate systems. Thus, there is an urgent need to develop high-energy-density LTM phosphate batteries.

[0004] Lithium transition metal oxides have high energy density. Using lithium transition metal oxides and transition metal phosphates together as positive electrode active materials can improve energy density. However, the fast charging performance and safety performance (high-temperature gas generation) after the composite system are combined become new problems. It is urgent to solve the problems of fast charging and high-temperature gas generation in the composite system. Summary of the Invention

[0005] In view of this, the main objective of the present invention is to provide an electrochemical device. This electrochemical device has improved safety and fast charging performance.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0007] A first aspect of the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, and an electrolyte. The positive electrode comprises a positive current collector and a positive electrode film disposed on at least one surface of the positive current collector. The positive electrode film comprises a positive electrode active material. The positive electrode active material comprises lithium transition metal phosphate and lithium transition metal oxide. The electrolyte comprises an additive and an organic solvent. The additive comprises 1,3-propane sulpholactone, and the organic solvent comprises a carboxylic acid ester solvent.

[0008] In some embodiments, the mass percentage of 1,3-propanesulfonyl lactone is represented as a based on the mass of the electrolyte; the mass percentage of carboxylic acid ester solvent is represented as b based on the mass of the organic solvent; and the mass percentage of lithium transition metal oxide is represented as c based on the mass of the positive electrode active material; a, b, and c satisfy 0.08 ≤ (a / (b+c))*10 ≤ 1.5.

[0009] In some implementations, a, b, and c satisfy 0.1 ≤ (a / (b+c))*10 ≤ 1.

[0010] In some embodiments, the mass percentage (a) of 1,3-propanesulfonyl lactone is 0.3% to 2% based on the mass of the electrolyte.

[0011] In some embodiments, the mass percentage (b) of the carboxylic acid ester solvent is 5% to 40% based on the mass of the organic solvent.

[0012] In some embodiments, the mass percentage (c) of lithium transition metal oxide is 5% to 40% based on the mass of the positive electrode active material.

[0013] In some embodiments, the additive also includes at least one of vinyl sulfate, vinylene carbonate, and fluorovinylene carbonate.

[0014] In some embodiments, the mass percentage of vinyl sulfate is 0.3% to 2% based on the mass of the electrolyte.

[0015] In some embodiments, the carboxylic acid ester solvent includes at least one of propyl propionate, ethyl propionate, propyl acetate, and ethyl acetate.

[0016] In some embodiments, the electrolyte further includes an electrolyte salt, including lithium hexafluorophosphate.

[0017] In some embodiments, the additive also includes lithium difluorooxalate borate.

[0018] In some embodiments, the mass percentage of lithium difluorooxalate borate is 0.1% to 1% based on the mass of the electrolyte.

[0019] In some embodiments, the structural formula of the lithium transition metal oxide includes:

[0020] Li d Ni a Co b Mn c M (1-a-b-c) Q z Where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5;

[0021] Element M includes at least one element selected from B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce.

[0022] The Q element includes at least one of O and F.

[0023] In some embodiments, the mass percentage of Ti element is 100 ppm to 600 ppm based on the mass of lithium transition metal oxide.

[0024] In this application, the positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide, enabling the electrochemical device to achieve both high energy density and high safety performance. This application simultaneously introduces carboxylic acid esters and 1,3-propane sulpholactone into the electrolyte. While carboxylic acid esters can significantly improve fast-charging performance, they undergo side reactions with lithium transition metal oxides at high voltages, leading to deterioration in high-temperature performance (safety performance). This application addresses this by introducing 1,3-propane sulpholactone, which forms a protective film on the positive electrode surface, blocking contact between the carboxylic acid ester solvent and the lithium transition metal oxide. This suppresses the side reactions between the carboxylic acid ester and the lithium transition metal oxide, improving the high-temperature performance of the electrochemical device, and thus further enhancing its safety performance. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0026] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0027] Unless otherwise specified, the term "or" is inclusive in this invention. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0028] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.

[0029] The first aspect of this application provides an electrochemical device. This electrochemical device can be a lithium-ion battery, a lithium metal battery, or, as described in the embodiments of this application, is not limited to this.

[0030] In this application, the electrochemical device includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector. The positive electrode film layer includes a positive electrode active material. The positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide. The electrolyte includes additives and an organic solvent. The additives include 1,3-propane sulpholactone, and the organic solvent includes a carboxylic acid ester solvent.

[0031] In this application, the positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide, enabling the electrochemical device to achieve both high energy density and high safety performance. This application simultaneously introduces carboxylic acid esters and 1,3-propane sulpholactone into the electrolyte. While carboxylic acid esters significantly improve fast-charging performance, they undergo side reactions with lithium transition metal oxides at high voltages, leading to deterioration in high-temperature performance (safety performance). This application addresses this by introducing 1,3-propane sulpholactone, which contains highly reactive epoxy groups. These groups can chemically react with lithium ions on the electrode surface and the solvent in the electrolyte. During the initial charge and discharge process of the electrochemical device, the epoxy groups can open their rings and react with lithium ions on the electrode surface, forming a CEI (Cathode-Electrolyte Interphase) film on the positive electrode surface. The CEI film blocks the contact between the carboxylic acid ester solvent and the lithium transition metal oxide, thereby suppressing the side reactions between the carboxylic acid ester and the lithium transition metal oxide, improving the high-temperature performance of the electrochemical device, and further enhancing its safety performance.

[0032] In this application, "lithium transition metal phosphates" typically have the chemical formula LiMPO4 (where M represents a transition metal, such as iron, manganese, nickel, cobalt, etc.). These compounds are widely used as cathode materials in electrochemical devices due to their excellent electrochemical performance. In lithium transition metal phosphates, lithium ions (Li... + As mobile cations, lithium ions migrate between the positive and negative electrodes during the charging and discharging process of the battery. The transition metal (M) and phosphate (PO4) constitute a stable crystal lattice structure, which provides excellent migration channels and a stable electronic structure for lithium ions. Lithium transition metal phosphates offer advantages such as high safety, long cycle life, and good environmental friendliness. Examples of lithium transition metal phosphates include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4, also known as LFP), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium iron manganese phosphate and carbon composites.

[0033] In this application, "lithium transition metal oxides" refers to a class of oxide compounds containing lithium (Li) and at least one transition metal (such as iron, cobalt, nickel, manganese, etc.). These compounds are commonly used as cathode materials in electrochemical devices because they can reversibly insert and extract lithium ions during the charging and discharging process of the battery. Lithium transition metal oxides exhibit high capacity.

[0034] Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.1 Al 0.05 At least one of O2 and its modified compounds.

[0035] In this application, "carboxylic acid ester solvent" refers to a class of organic compounds containing a carboxylic acid ester functional group, chemically represented as R-COO-R', where R and R' are carbon chains, which can be the same or different, and at least one is a hydrocarbon chain. Carboxylic acid ester solvents typically have high ionic conductivity, meaning they can better support the migration of lithium ions in the electrolyte. Using carboxylic acid ester solvents can significantly improve the fast-charging performance of electrochemical devices.

[0036] In some embodiments, the mass percentage of 1,3-propanesulfonyl lactone, based on the mass of the electrolyte, is denoted as 'a'; the mass percentage of carboxylic acid ester solvent, based on the mass of the organic solvent, is denoted as 'b'; and the mass percentage of lithium transition metal oxide, based on the mass of the positive electrode active material, is denoted as 'c'. a, b, and c satisfy the following condition: 0.08 ≤ (a / (b+c))*10 ≤ 1.5, and optionally, 0.1 ≤ (a / (b+c))*10 ≤ 1. In this implementation, by controlling the proportions of 1,3-propanesulfonyl lactone, carboxylic acid ester solvent, and lithium transition metal oxide, the interfacial interaction between the electrolyte and the positive electrode material can be optimized. This facilitates the formation of a uniform and moderately thick CEI film on the surface of the positive electrode, thereby improving the safety performance of the electrochemical device while also considering its internal resistance. For example, (a / (b+c))*10 is 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 0.1, 1.1, 1.2, 1.3, 1.4, 1.5 or any value between two values.

[0037] The following is a further explanation of the components of the electrochemical device:

[0038] electrolytes

[0039] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0040] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt, additives, and an organic solvent.

[0041] In some embodiments, the electrolyte comprises an organic solvent, including a carboxylic acid ester solvent. Carboxylic acid ester solvents typically have good ionic conductivity and can provide high ion mobility, thereby improving the fast-charging performance of the electrochemical device.

[0042] In some embodiments, the mass percentage b of the carboxylic acid ester solvent, based on the mass of the organic solvent, is 5% to 40%. The mass percentage of the carboxylic acid ester solvent can adjust the viscosity of the electrolyte. By controlling the mass percentage of the carboxylic acid ester solvent within the above range, it is beneficial to avoid the electrolyte becoming too viscous, which could adversely affect ion transport, while also preventing the electrolyte from becoming too thin, which could easily lead to evaporation or leakage. For example, the mass percentage b of the carboxylic acid ester solvent, based on the mass of the organic solvent, is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or any value between two of these.

[0043] In some embodiments, the additives also include at least one of vinyl sulfate, vinylene carbonate, and fluorovinylene carbonate. These additives can form a uniform and stable CEI film on the positive electrode, which effectively reduces electron transport resistance, thereby reducing the internal resistance of the electrochemical device and improving its fast-charging performance.

[0044] In some embodiments, the mass percentage of vinyl sulfate in the electrolyte is 0.3% to 2%, optionally 0.5% to 1.5%. When the mass percentage of vinyl sulfate in the electrolyte is within the above range, a uniform and stable CEI film can be formed on the surface of the positive electrode. This CEI film can effectively isolate the electrolyte from contact with lithium transition metal oxides, reducing the occurrence of side reactions inside the electrochemical device, thereby improving the safety performance of the electrochemical device. Exemplarily, the mass percentage of vinyl sulfate in the electrolyte is 0.3%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, or any value between two of these values.

[0045] In some embodiments, the carboxylic acid ester solvent includes at least one selected from propyl propionate, ethyl propionate, propyl acetate, and ethyl acetate. These carboxylic acid ester solvents exhibit good solubility for electrolyte salts, and their selection facilitates good ionic conductivity. Furthermore, these carboxylic acid ester solvents possess good thermal and electrochemical stability, thus contributing to improved safety performance of the electrochemical device.

[0046] In some embodiments, the organic solvent may also include at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate.

[0047] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiTFSI), lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethylsulfonyl)methyl, or lithium bis(trifluoromethylsulfonyl)imide.

[0048] In some embodiments, the electrolyte salt includes lithium hexafluorophosphate, which possesses excellent ion conductivity. Using lithium hexafluorophosphate as the electrolyte salt can further enhance the overall ion conductivity, thereby ensuring that lithium ions can migrate efficiently and effectively in the electrolyte, thus improving the fast-charging performance of the electrochemical device.

[0049] In some embodiments, the additive also includes lithium difluorooxalate borate. Lithium difluorooxalate borate can form a stable CEI film on the surface of the positive electrode. This CEI film effectively reduces electron transport resistance, thereby reducing the internal resistance of the electrochemical device and improving its fast-charging performance.

[0050] In some embodiments, the mass percentage of lithium difluorooxalate borate is 0.1% to 1% based on the mass of the electrolyte. Controlling the mass percentage of lithium difluorooxalate borate within this range facilitates the formation of a uniform and stable CEI film on the surface of the positive electrode. This CEI film effectively isolates the electrolyte from contact with lithium transition metal oxides, reducing the occurrence of side reactions within the electrochemical device and thereby improving the safety performance of the electrochemical device. Exemplarily, the mass percentage of lithium difluorooxalate borate is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any value between two of these values, based on the mass of the electrolyte.

[0051] In some embodiments, the electrolyte includes an additive, which includes 1,3-propanesulfonyl lactone, wherein the mass percentage (a) of 1,3-propanesulfonyl lactone is 0.3% to 2% by mass of the electrolyte. By controlling the mass percentage of 1,3-propanesulfonyl lactone within the above range, it is beneficial to form a CEI film of moderate thickness on the surface of the positive electrode. This moderately thick CEI film helps to block the contact between the carboxylic acid ester solvent and the lithium transition metal oxide, while also reducing the influence of the CEI film on the internal resistance of the electrochemical device, thereby balancing safety performance and fast charging performance.

[0052] For example, the mass percentage a of 1,3-propanesulfonyl lactone, based on the mass of the electrolyte, is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, or any value between two of these values.

[0053] In some embodiments, the additives may also include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain performance of the electrochemical device, such as additives that improve the overcharge performance of the electrochemical device, additives that improve the high-temperature or low-temperature performance of the electrochemical device, etc.

[0054] Positive electrode sheet

[0055] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0056] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0057] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0058] In this application, the positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide.

[0059] In some embodiments, the particle size distribution of the positive electrode active material is between 0.2 μm and 0.4 μm. Exemplarily, the particle size distribution of the positive electrode active material is 0.2 μm, 0.21 μm, 0.22 μm, 0.23 μm, 0.24 μm, 0.25 μm, 0.26 μm, 0.27 μm, 0.28 μm, 0.29 μm, 0.31 μm, 0.32 μm, 0.33 μm, 0.34 μm, 0.35 μm, 0.36 μm, 0.37 μm, 0.38 μm, 0.39 μm, 0.4 μm, or any value between two of these two values.

[0060] In some embodiments, the mass percentage (c) of lithium transition metal oxide, based on the mass of the positive electrode active material, is 5% to 40%. By controlling the mass percentage of lithium transition metal oxide within the above range, it is beneficial to improve the energy density and electrochemical performance of the electrochemical device, while also improving the safety performance of the electrochemical device. For example, the mass percentage (c) of lithium transition metal oxide, based on the mass of the positive electrode active material, is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or any value between two of these values.

[0061] In some embodiments, the lithium transition metal phosphate comprises lithium transition metal phosphate particles, which include a lithium transition metal phosphate matrix and a coating layer on at least a portion of the surface of the lithium transition metal phosphate matrix, the coating layer comprising carbon. Using the aforementioned lithium transition metal phosphate particles as the positive electrode active material is beneficial for improving the cycle life of the electrochemical device.

[0062] In some embodiments, the chemical formula of the lithium transition metal phosphate matrix is ​​Li x1 Ay1 Me a1 M b1 P 1-c1 X c1 Y z1 Wherein, 0.5≤x1≤1.3, 0≤y1≤0.8, 0.9≤x1+y1≤1.3, 0.9≤a1≤1.5, 0≤b1≤0.5, 0.9≤a1+b1≤1.5, 0≤c1≤0.5; 3≤z1≤5, A includes one or more of Na, K and Mg; Me includes one or more of Mn, Fe, Co and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La and Ce; X includes one or more of S, Si, Cl, B, C, N and P; Y includes one or more of O and F.

[0063] In some implementations, lithium transition metal phosphates include lithium iron phosphate.

[0064] In some embodiments, the structural formula of the lithium transition metal oxide includes: Li d Ni a Co b Mn c M (1-a-b-c) Q z Wherein, 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5; element M includes at least one element selected from B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce; element Q includes at least one element selected from O and F. Nickel has a relatively low atomic weight, but its oxidation state can vary considerably, meaning that each unit mass of nickel can store more lithium ions. In this lithium transition metal oxide, 0.6 < a < 1 reflects that the lithium transition metal oxide has a large number of nickel atoms, therefore, this lithium transition metal oxide has a high theoretical capacity, and using this lithium transition metal oxide as a positive electrode active material is beneficial for improving the energy density of electrochemical devices.

[0065] In some embodiments, the mass percentage of Ti, based on the mass of the lithium transition metal oxide, is between 100 ppm and 600 ppm. By selecting a lithium transition metal oxide with a Ti mass percentage within this range, the lithium-ion transport barrier can be lowered, the lithium-ion diffusion rate can be increased, thereby improving the kinetic performance of the electrochemical device and enhancing cycle performance. Exemplarily, the Ti mass percentage is 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, or any value between two of these ranges.

[0066] During the charging and discharging process of electrochemical devices, Li undergoes deintercalation and deintercalation, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. When the positive electrode active material is applied to the electrochemical device system, the molar Li content changes after charge-discharge cycles.

[0067] In the examples of positive electrode active materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.

[0068] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0069] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0070] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0071] Negative electrode sheet

[0072] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0073] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0074] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0075] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in electrochemical devices. As an example, the negative electrode active material may include at least one of the following materials: graphite materials, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Graphite materials may be selected from at least one of artificial graphite and natural graphite. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials in electrochemical devices may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0076] In some embodiments, the negative electrode active material includes graphite. Graphite has good cycling performance and can withstand multiple charge-discharge cycles without significant structural changes, thus helping to extend the service life of the electrochemical device.

[0077] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0078] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0079] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0080] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0081] Separating membrane

[0082] In some embodiments, the electrochemical device also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0083] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0084] In some embodiments, the separator includes a base membrane, ceramic layers disposed on both sides of the base membrane, and an adhesive layer disposed on at least one side of the ceramic layer away from the base membrane.

[0085] In some embodiments, the base film may be made of one or more of the following materials, including but not limited to glass fiber, nonwoven fabric, polyethylene (PE), and polypropylene (PP).

[0086] In some embodiments, the ceramic layer includes one or more of alumina (Al2O3), zirconium oxide (ZrO2), titanium oxide (TiO2), silicon oxide (SiO2), and boron nitride (BN).

[0087] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0088] In some embodiments, the electrochemical device may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0089] In some embodiments, the outer packaging of the electrochemical device can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the electrochemical device can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0090] Example

[0091] The preparation method of the electrochemical device is as follows:

[0092] (1) Preparation of negative electrode sheet

[0093] A negative electrode active material (artificial graphite), conductive carbon (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed in deionized water at a weight ratio of 96.4:1:1.2:1.4 and stirred until homogeneous to obtain a negative electrode slurry. Copper foil was used as the negative electrode current collector, and the negative electrode slurry was coated onto one side of the current collector. The coating was baked at 120°C for 1 hour, followed by cold pressing, cutting, and slitting to prepare the negative electrode, wherein the thickness of the negative electrode active layer was 100 μm.

[0094] (2) Preparation of positive electrode sheet

[0095] Lithium transition metal phosphate (LiFePO4, particle size 0.35μm±0.20μm) and lithium transition metal oxide (Li1Ni) were used. 0.79955 Co 0.10 Mn 0.10 Ti 0.00045 The positive electrode active material is obtained by mixing O2 and Ti (450 ppm by mass) at a mass ratio of 90:10.

[0096] The positive electrode active material, conductive carbon (SP), carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were mixed in N-methylpyrrolidone solvent at a weight ratio of 96.3:0.7:1:2 and stirred until homogeneous to obtain a positive electrode slurry. Aluminum foil was used as the positive electrode current collector. The slurry-coated current collector was dried at 85°C, followed by cold pressing, cutting, and slitting to prepare the positive electrode.

[0097] (3) Preparation of electrolytes

[0098] In an argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and carboxylic acid ester (ethyl acetate, EA) are mixed to obtain an organic solvent. The mass ratio of EC, EMC, DMC, and EA in the organic solvent is 3:1:5:1.

[0099] Then add vinyl sulfate (DTD), vinylene carbonate (VC), and fluorovinylene carbonate (FEC).

[0100] Then add 1,3-propanesulfonyl lactone (PS), and finally add lithium hexafluorophosphate (LiPF6) to obtain the electrolyte.

[0101] Based on the mass of the electrolytes, PS accounts for 0.5%, LiPF6 accounts for 12.5%, DTD accounts for 0.5%, VC accounts for 1%, and FEC accounts for 0.5%.

[0102] (4) Preparation of the separating membrane

[0103] A polyethylene film with a thickness of 7 μm is used as the substrate. A PVDF coating with a thickness of 5 μm is applied to both sides of the substrate. A boehmite ceramic layer with a thickness of 3 μm is applied to one of the PVDF coated surfaces to obtain the isolation membrane.

[0104] (5) Assembly of electrochemical devices

[0105] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The side of the separator coated with boehmite ceramic layer is aligned with the positive electrode. The positive electrode, separator, and negative electrode are then stacked, placed in an aluminum-plastic film, dried at 80°C, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, the electrochemical device is obtained.

[0106] The performance of the obtained electrochemical device was tested using the following methods:

[0107] Fast charging performance test:

[0108] The electrochemical device was placed in a constant temperature chamber at 25°C and left to stand for 30 minutes. It was then charged at a constant charging rate of 0.5C to the charging cutoff voltage, and then charged at a constant voltage to a charging rate of 0.05C. After standing for 5 minutes, the device was allowed to stand.

[0109] Then, after storing in a 60℃ oven for 30 days, take it out and place it in a 25℃ constant temperature box for 30 minutes. Charge it to 4.25V at a constant charging rate of 4C, then charge it to 0.05C at a constant voltage, let it stand for 5 minutes, and then discharge it to 2.5V at a constant discharge rate of 1.0C.

[0110] Repeat the above steps 10 times, let stand for 5 minutes, charge at a constant charging rate of 4C to 4.25V, then charge at a constant voltage to a charging rate of 0.05C, disassemble the negative electrode, and observe the lithium deposition.

[0111] Basis for judgment:

[0112] The presence of metallic lithium deposition on a large surface area of ​​the negative electrode indicates severe lithium deposition on the negative electrode, resulting in poor fast-charging performance of the electrochemical device.

[0113] The presence of metallic lithium deposition at the edge of the negative electrode indicates lithium deposition at the edge of the negative electrode, which improves the fast charging performance of the electrochemical device.

[0114] No metallic lithium was deposited on the surface of the negative electrode, indicating that the negative electrode does not deposit lithium, and the fast charging performance of the electrochemical device is further improved.

[0115] Testing of high-temperature gas production performance:

[0116] Place the electrochemical device in a constant temperature chamber at 25°C for 30 minutes, and then perform the test as follows:

[0117] 1) Let stand for 5 minutes;

[0118] 2) Charge at a constant charging rate of 4C to 4.25V; then charge at a constant voltage to a charging rate of 0.05C;

[0119] 3) Let stand for 5 minutes;

[0120] 4) Discharge to 2.5V at a constant discharge rate of 1.0C;

[0121] 5) Repeat steps 1) to 4) 100 times;

[0122] The electrochemical devices were placed in a constant temperature chamber at 25°C and left to stand for 30 minutes. The volume V0 of each device was measured using the Archimedes displacement method. The devices were then charged at a constant current of 0.33C to 4.25V, followed by constant voltage charging to 0.05C. The devices were then placed in a 60°C incubator for thermal storage. After 30 days, the devices were removed and their volume was measured using the Archimedes displacement method, which was V30. The volume growth rate of the electrochemical devices was calculated as (V30 - V0) / V0 * 100%.

[0123] The volume growth rate of an electrochemical device is used to reflect its safety performance. A high volume growth rate indicates poor safety performance, while a low volume growth rate indicates good safety performance.

[0124] Examples 2 to 13

[0125] Examples 2 to 13 were prepared using the same method as in Example 1, except that, according to Table 1, at least one of the following was adjusted: the mass percentage of 1,3-propanesulfonyl lactone (a), the mass percentage of lithium transition metal oxide (c), the type or mass percentage of carboxylic acid ester solvent (b), and the mass percentage of vinyl sulfate (DTD).

[0126] Example 14

[0127] Example 14 uses the same method as Example 1 to prepare an electrochemical device, except that lithium difluorooxalate borate (LiODFB) with a mass ratio of 0.3% based on the mass of the electrolyte is added in the preparation of the electrolyte, and the mass ratio a of 1,3-propane sulpholactone and the mass ratio b of the carboxylic acid ester solvent are adjusted according to Table 1.

[0128] Example 15

[0129] Example 15 uses the same method as Example 1 to prepare an electrochemical device, except that lithium difluorooxalate borate (LiODFB) with a mass ratio of 0.5% based on the mass of the electrolyte is added in the preparation of the electrolyte, and the mass ratio a of 1,3-propane sulpholactone and the mass ratio b of the carboxylic acid ester solvent are adjusted according to Table 1.

[0130] Comparative Example 1

[0131] Comparative Example 1 used the same method as Example 1 to prepare an electrochemical device, except that no carboxylic acid ester solvent (ethyl acetate, EA) and 1,3-propanesulfonyl lactone were added in the preparation of the electrolyte.

[0132] Comparative Example 2

[0133] Comparative Example 2 used the same method as Example 1 to prepare an electrochemical device, except that 1,3-propanesulfonyl lactone was not added in the preparation of the electrolyte.

[0134] Comparative Example 3

[0135] Comparative Example 3 used the same method as Example 1 to prepare an electrochemical device, except that no carboxylic acid ester solvent (ethyl acetate, EA) was added in the preparation of the electrolyte.

[0136] The electrochemical devices obtained in Examples 2 to 15 and Comparative Examples 1 to 3 were tested using the same test methods as in Example 1. The test results are shown in Table 1 below.

[0137] Table 1

[0138]

[0139] In Table 1, " / " indicates that no related items have been set. a represents the mass percentage of 1,3-propanesulfonyl lactone based on the mass of the electrolyte. b represents the mass percentage of carboxylic acid ester solvent based on the mass of the organic solvent. c represents the mass percentage of lithium transition metal oxide based on the mass of the positive electrode active material.

[0140] As can be seen from the data in Table 1, compared with the electrochemical devices prepared in Comparative Examples 1 to 3, the electrochemical devices prepared in Examples 1 to 15 have improved fast-charging performance and safety performance.

[0141] By comparing Examples 1 to 9 with Examples 10 to 11, it can be seen that when (a / (b+c))*10 satisfies 0.1 to 1, the fast-charging performance of the electrochemical device is improved.

[0142] The data from Examples 4, 12, and 13 show that further increasing the DTD content can further reduce the gas production of the electrochemical device, thereby further improving the safety performance of the electrochemical device.

[0143] As can be seen from the data in Examples 14 and 15 and Example 4, the introduction of LiODFB can further reduce the gas production of the electrochemical device, thereby further improving the safety performance of the electrochemical device.

[0144] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. An electrochemical device, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes a positive electrode active material. The positive electrode active material includes lithium transition metal phosphate and lithium transition metal oxide; The electrolyte includes additives and organic solvents, the additives including 1,3-propanesulfonyl lactone, and the organic solvents including carboxylic acid ester solvents.

2. The electrochemical device according to claim 1, characterized in that, The mass percentage of 1,3-propanesulfonyl lactone, based on the mass of the electrolyte, is expressed as a; The mass percentage of the carboxylic acid ester solvent, based on the mass of the organic solvent, is expressed as b. The mass percentage of the lithium transition metal oxide, based on the mass of the positive electrode active material, is expressed as c; The terms a, b, and c satisfy 0.08 ≤ (a / (b+c))*10 ≤ 1.

5.

3. The electrochemical device according to claim 2, characterized in that, The terms a, b, and c satisfy 0.1 ≤ (a / (b+c))*10 ≤ 1.

4. The electrochemical device according to claim 2 or 3, characterized in that, The mass percentage (a) of the 1,3-propanesulfonyl lactone, based on the mass of the electrolyte, is 0.3% to 2%, and / or, Based on the mass of the organic solvent, the carboxylic acid ester solvent accounts for 5% to 40% of the total mass, and / or, Based on the mass of the positive electrode active material, the mass percentage (c) of the lithium transition metal oxide is 5% to 40%.

5. The electrochemical device according to any one of claims 1 to 4, characterized in that, The additives also include at least one of vinyl sulfate, vinylene carbonate, and fluorovinylene carbonate.

6. The electrochemical device according to claim 5, characterized in that, The ethylene sulfate content is 0.3% to 2% by mass of the electrolyte.

7. The electrochemical device according to any one of claims 1 to 6, characterized in that, The carboxylic acid ester solvent includes at least one of propyl propionate, ethyl propionate, propyl acetate, and ethyl acetate.

8. The electrochemical device according to any one of claims 1 to 7, characterized in that, The electrolyte also includes an electrolyte salt, which includes lithium hexafluorophosphate.

9. The electrochemical device according to any one of claims 1 to 8, characterized in that, The additives also include lithium difluorooxalate borate.

10. The electrochemical device according to claim 9, characterized in that, The lithium difluorooxalate borate accounts for 0.1% to 1% of the mass of the electrolyte.

11. The electrochemical device according to any one of claims 1 to 10, characterized in that, The structural formula of the lithium transition metal oxide includes: Li d Ni a Co b Mn c M (1-a-b-c) Q z Where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c <1,1.8≤z≤3.5; Element M includes at least one element selected from B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce. The Q element includes at least one of O and F.

12. The electrochemical device according to claim 11, characterized in that, The mass percentage of Ti element is 100 ppm to 600 ppm based on the mass of the lithium transition metal oxide.